Comportamento de uma massa coluvial - Costa, Douglas Pereira da (2017)
It presents a case of geological environment whose predisposing agents favor in a significant way the movements of the slope. It is a colluvial mass with the opposite side of the slope working as a basin of rainfall accumulation. The water preferably seeps into cracks in the rocks, that dip into the direction of the colluvium base. In addition to the unfavourable geological and hydrological aspects to the stability of the slope, in mid1976, there was an excavation in the area to implement a highway. Since then, there have been significant creep movements in the area with controlled seasonality by changes in the water table. The slope behavior has been monitored since the end of 2011. The instrumentation consists of surface measuring marks, inclinometers, pluviographs, water level meters, Casagrande piezometers and electrical piezometers, as well as the monitoring of deep horizontal drains (DHDs). Geotechnical profiles have been defined based on the results from rotary drilling and topographic and geophysical survey. The soil parameters were determined by tests made in undisturbed soil samples and verified by back analysis. Correlation studies between instrumentation data showed that there is a strong relationship between rainfall, variations in water table level, DHD’s discharge and slope movement. Stability analyzes indicated that the colluvial mass Safety Factor can reach acceptable values with the lowering of the water table level, interrupting the movement.